O Quilombismo de Abdias Nascimento: fundamentos para uma educação antirracista - Rocha, Fabiana de Oliveira Maciel (2021)
The following master's thesis aims to investigate the assumptions of Abdias Nascimento's thought, the ideals and proposals that point to actions for an anti-racist education. This is done from considerations of the work O Quilombismo ([1980] 2019) based on what advocates the teaching of Afro-Brazilian and African history resuming the quilombist precepts defended by the author. The object of study is composed of an analysis of the potentialities of the term Quilombism produced by Abdias together with a qualitative bibliographical study of the author's production. The dissertation is inserted in the field of historiographical studies about the history of intellectuality, a branch of the history of mentalities that focuses on the history of thoughts and ideas. We outline as a hypothesis the observation of a projection of Abdias' proposal to fight racism, having education as a platform for action. In other words, the fight against racism for Abdias would occur through education by incorporating assumptions of Quilombism. Under such reading, it can be affirmed that Quilombism is a creation from the black diaspora whose application in education can project the constitution of an antiracist education.